Development of Ternary Cathodes Using MyCe1–x–yMnxO2–δ (M = La, Gd) as Catalysts for Oxygen Reduction Reactions1. Issue 3 (6th February 2014) - Liu, L.; Zhao, Z.; Zhang, X.; Cui, D.; Tu, B.; Ou, D.; Cheng, M.; Steiner, Nadia; Hissel, Daniel; Bultel, Yann
Abstract MyCe1–x–yMnxO2–δ (M = La, Gd) oxides have been investigated as oxygen reduction catalysts for LSM–YSZ based ternary cathodes. MyCe1–x–yMnxO2–δ samples are characterized by X‐ray diffraction (XRD), temperature programmed reduction of H2 (H2‐TPR), and temperature programmed desorption of O2 (O2‐TPD). The results show that the incorporation of M (M = La, Gd) ions increases the solution limit of Mn in the solid solutions, which increases the amount of oxygen vacancies and promotes oxygen adsorption and dissociation processes. The ternary cathodes show much higher electrochemical performance than LSM–YSZ binary cathode, and greatly accelerate oxygen dissociative adsorption and diffusion of oxygen species. The MyCe1–x–yMnxO2–δ catalysts exhibit greatly high activity for oxygen reduction at intermediate temperature. The ternary cathodes have high stability and high resistance to CO2 at 600 °C.